Eros and Thanatos: A psychoanalytic examination of death in the context of working life - Kahn, Susan (Eros i Tanatos: psychoanalityczna perspektywa śmierci w kontekście miejsca pracy, 2016)
The unpredictability of work and the absence of lifetime institutions forces us to confront our occupational mortality. This paper grapples with the instinct towards life; Eros; and towards destruction; Thanatos;1 in the context of working life. It deals with death and explores the consequences of an anticipated workplace mortality. This paper brings a fresh approach to understanding organizational endings through the application of psychoanalytic notions of death. First I present the theoretical basis of death in psychoanalysis: the death drive and mourning and melancholia. I then examine the treatment of death in organizations before briefly applying the theory to a research case based in the City of London post the 2008 financial crisis
Management Forum, 2016, vol. 4, no. 3, s. 29-40
Keywords: Thanatos; death drive; mourning and melancholia; organizational endings; popęd śmierci; żałoba i melancholia; koniec życia organizacji